Pendampingan Pengolahan Bawang Goreng dan Peningkatan Kualitas dengan Penerapan Mesin Semi Otomatis pada KWT Permata Tani Desa Rubaru Kecamatan Rubaru Kabupaten Sumenep - Hopid Hopid; Arda Gusema Susilowati; Isdiantoni Isdiantoni; Djoko Suwito; Andre Dwijanto Witjaksono; Dhita Ayu Permata Sari (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
The Permata Tani Women Farmers Group (KWT) in Rubaru Village, Rubaru Subdistrict, Sumenep Regency, has great potential in processing local varieties of shallots into fried shallots, but faces various obstacles in terms of product quality, production efficiency, and marketing. The main problems include uneven shallot slices, dark colour, oily texture, and unattractive and uninformative packaging. A community service programme (Kosabangsa) using an integrated approach was implemented to improve the capacity of KWT through the application of appropriate technology such as peeling machines, slicers, fryers, and oil strainers, as well as assistance in hygienic production, branding and packaging development, business literacy, simple financial record keeping, and digital and conventional marketing strategies. The results showed a significant increase in production process efficiency (chopping time reduced from 30 minutes to 5 minutes per kilogram and more uniform slices), product quality (drier, crispier, and less oily), and competitiveness through the launch of the local brand ‘Bawang Goreng Krowes’ (Krowes Fried Onions). Additionally, strengthening the group's institutional capacity, developing standard operating procedures (SOP), and establishing strategic partnerships with the village government and universities ensured the sustainability of the business. This programme has successfully transformed KWT Permata Tani from a household business into a professional, sustainable, and competitive micro-agroindustry, while also strengthening the role of women in the local economy. This empowerment model has the potential to be replicated in similar areas.